Writing Experience: The Vietnam Veteran and his literary Voice - Araujo (UFMG), Fabricio Paiva (ANTARES: Letras e Humanidades, 2014)
The way Vietnam War veterans write about their war experiences, the reasons that led them to write about them and the meaning of writing such accounts are the main purpose presented in this article. The vets' accounts are often the result of what they saw, lived and suffered because of the Vietnam War. Therefore, historical and cultural approaches are used to show the importance of this historical moment in the characters' lives. The vets' accounts must be considered a legacy of great significance to understand the war narratives through their historical context and to understand cultural and intellectual history through literature. Finally, the article intends to show that the representation of the vets' experiences in war narratives is also the result of the vets' strength to transform the traumas of their war experiences into something meaningful.